2021
DOI: 10.3390/healthcare9010075
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Behavioral Changes Since COVID-19 among Middle School Students

Abstract: Middle school students are of particular interest when examining the impact of the COVID-19 pandemic because they are in a formative period for socioemotional development, and because they are not as mature as adults, making them more vulnerable to the effects of the current pandemic. This study seeks to examine determinants of protective behavior changes since COVID-19 among middle school students. Participants were recruited through an official online flatform used by public schools. The final sample include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…There are numerous studies describing and investigating compliance with Covid-19 measures in various countries, particularly for the US [2][3][4][5][6][7], Germany [8], Italy [9], Switzerland [1,10], Slovakia [11], Israel [12], South Korea [13], Japan [14], Indonesia [15], or Co ˆte d'Ivoire [16]. Even though many of these studies only use opportunity samples or student samples, a few consistent results have still emerged.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There are numerous studies describing and investigating compliance with Covid-19 measures in various countries, particularly for the US [2][3][4][5][6][7], Germany [8], Italy [9], Switzerland [1,10], Slovakia [11], Israel [12], South Korea [13], Japan [14], Indonesia [15], or Co ˆte d'Ivoire [16]. Even though many of these studies only use opportunity samples or student samples, a few consistent results have still emerged.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there are also some socio-demographic differences. Thus, women adhere more often to preventive measures than do men [1,5,7,10,[13][14][15]. Less consistent are the findings concerning age.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Korea, there have been nearly 97,000 confirmed cases and 1,700 confirmed deaths from COVID-19 since the country's first reported case in January 2020 (Centers for Disease Control and Prevention, 2021). Social distancing measures to prevent the spread of the virus have greatly affected everyone, but adolescents are particularly affected by prevention measures such as the transition to online schooling (Lee et al, 2021). Research has shown that knowledge regarding the risk of COVID-19 is associated with increased engagement in protective behaviors among middle school students (Lee et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Social distancing measures to prevent the spread of the virus have greatly affected everyone, but adolescents are particularly affected by prevention measures such as the transition to online schooling (Lee et al, 2021). Research has shown that knowledge regarding the risk of COVID-19 is associated with increased engagement in protective behaviors among middle school students (Lee et al, 2021). Thus, it is of interest to examine what factors may influence middle school students’ knowledge of COVID-19, including their access to Information and Communication Technology (ICT) resources, such as broadband internet, computers, or tablets, as well as their relationship with family members, as COVID-19 preventive social distancing measures have caused people to spend more time at home with family, as well as to rely on ICT resources to attend school or work or to safely communicate with people outside their immediate household (Fegertet al, 2020; Wiederhold, 2020).…”
Section: Introductionmentioning
confidence: 99%